Diatoms, sedimentology and geochemistry study from a high altitude lake in the Fuegian Andes - Fernández, Marilén (2022)
In order to analyze environmental and climatic changes during the late Holocene, a lacustrine sediment core was obtained from Laguna Ceniza (54˚ 40’ 38” S; 68˚ 13’ 13” O) located in a hanging valley in the Fuegian Andes (Argentina). The lake is fed by a stream originating from a small cirque glacier located in the valley head. The core (75 cm) was taken close to a delta of the stream and covers the last 2775 cal years BP. Here, we present the preliminary results based on sedimentological, geochemical and diatom data from the upper part of the core (last 1500 cal years BP). The sedimentological analysis shows the presence of six lithofacies: grey silty-sand, reddle silty-sand, laminated sandy-silt, laminated silt, grey clay-silt and white clay-silt. These lithofacies are likely associated to variations in the relative importance of glacier dynamics and mass movement processes from the valley slopes. The geochemical data (ITRAX core scanner) show a general decrease in the Al-Ti towards the top, and throughout the core there are several distinct peaks in Ca-Sr (possibly indicating input from the glacier). The diatom assemblages show a variety of species mainly dominated by Pinnularia microstauron (60 %) and P. interrupta, P. viridiformis, Aulacoseira alpigena, Brachysira huitatorum, Encyonema difficilis, Frustulia aff fuegiana, F. rhomboides and Veigaludwigia urbana in lower frequency (20%). In general, these taxa indicate a freshwater basin with oligotrophic conditions. At 16-17 cm of the core (900 cal years BP), Achnanthidium minutisimum reaches a frequency of 40%, together with an increase of Psammothidium incognitum (28%) and P. confusum (9%). The clear rise in the mentioned diatoms is associated to the reddle silty sand lithofacie, suggesting the occurrence of a highenergy flow event into the lake.